1999
DOI: 10.1897/1551-5028(1999)018<1791:soeaiu>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Estrogenic Activity in United Kingdom Estuarine and Coastal Waters and Its Effects on Gonadal Development of the Flounder Platichthys Flesus

Abstract: Abstract-Estrogenic discharges are known or suspected to be present in many United Kingdom estuaries and are also occurring from offshore oil and gas installations. The aim of this study was to establish whether estrogens and their mimics are present in marine waters at concentrations that can produce biological responses in fish and, if so, to discover whether the effects are likely to be harmful to populations and communities through changes in reproductive and other physiological processes. Laboratory studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
1
8

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(163 citation statements)
references
References 34 publications
6
148
1
8
Order By: Relevance
“…This demonstrated elevated concentrations of the female egg-yolk protein precursor vitellogenin (VTG) in the blood plasma of caged male trout (Oncorhynchus mykiss) that were placed in UK rivers -especially near sewage treatment works (Purdom, Hardiman, Bye, Eno, Tyler, & Sumpter, 1994). The finding was extended by Cefas to male flounders (Platichthys flesus) in UK estuaries in the 1990s (Allen, Matthiessen, Scott, Haworth, Feist, & Thain, 1999a;Allen, Scott, Matthiessen, Haworth, Thain, & Feist, 1999b) and to cod (Gadus morhua) in the open sea within the last five years (Scott, Katsiadaki, Witthames, Hylland, Davies, McIntosh et al, 2006b). …”
Section: Introductionmentioning
confidence: 97%
“…This demonstrated elevated concentrations of the female egg-yolk protein precursor vitellogenin (VTG) in the blood plasma of caged male trout (Oncorhynchus mykiss) that were placed in UK rivers -especially near sewage treatment works (Purdom, Hardiman, Bye, Eno, Tyler, & Sumpter, 1994). The finding was extended by Cefas to male flounders (Platichthys flesus) in UK estuaries in the 1990s (Allen, Matthiessen, Scott, Haworth, Feist, & Thain, 1999a;Allen, Scott, Matthiessen, Haworth, Thain, & Feist, 1999b) and to cod (Gadus morhua) in the open sea within the last five years (Scott, Katsiadaki, Witthames, Hylland, Davies, McIntosh et al, 2006b). …”
Section: Introductionmentioning
confidence: 97%
“…High levels of VTG (up to 20 mg ml -1 plasma) have also been measured in male flounder from other heavily industrialized British estuaries. In contrast, levels of VTG were low or undetectable in male flounder from estuaries draining rural areas, or from urban areas with relatively little heavy industrial activity Allen et al, 1999aAllen et al, , 1999b.…”
Section: Fishmentioning
confidence: 94%
“…In particular, Purdom et al [1] had shown that one of the steroid estrogens, the pharmaceutical ethinyl estradiol (EE2), was extraordinarily active in fish: very low to sub-ng/L concentrations induced vitellogenin synthesis in a concentration-dependent manner. Perhaps of even greater surprise, some estuaries proved to be estrogenic [6], although the causative chemicals were not identified at the time and have not been since.…”
Section: Answering the Important Challengesmentioning
confidence: 99%
“…It would be difficult to think of a more environmentally relevant parameter than reproduction when attempting 2084 All Supplemental Data may be found in the online version of this article. See Table S1 for the number of citations and rank of all the ''Top 100'' papers, which in this essay are references [3][4][5][6][7][9][10][11][12][13][14][15]19,20].…”
Section: Answering the Important Challengesmentioning
confidence: 99%